2013
DOI: 10.1097/bpb.0b013e3283623b2c
|View full text |Cite
|
Sign up to set email alerts
|

The successful treatment of genu recurvatum as a complication following eight-Plate epiphysiodesis in a 10-year-old girl

Abstract: We report a case of genu recurvatum following eight-Plate epiphysiodesis and the successful treatment of this complication. A 10-year-old patient underwent epiphysiodesis of the knee with eight-Plates. She was followed up and genu recurvatum developed as a complication. At the 12-month follow-up after epiphysiodesis, the treated knee showed a flexion of 135° and an extension of 35°. Lateral radiograph evaluation showed an extension change of the femur. During reoperation, the eight-Plates were repositioned mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This technique allows timing to be less precise and the leg lengths to be equalized at an earlier age, as long as the tension implant is removed in a 2-year time period [18]. Complications include inducing deformity at the joint due to placement of the tension device anterior or posterior to the center of the lateral physis and can be corrected by repositioning the implants [19]. Long-term outcomes of temporary epiphysiodesis are favorable, with deformities corrected during treatment time with removing one side of the tether [20].…”
Section: Growth Modulationmentioning
confidence: 99%
“…This technique allows timing to be less precise and the leg lengths to be equalized at an earlier age, as long as the tension implant is removed in a 2-year time period [18]. Complications include inducing deformity at the joint due to placement of the tension device anterior or posterior to the center of the lateral physis and can be corrected by repositioning the implants [19]. Long-term outcomes of temporary epiphysiodesis are favorable, with deformities corrected during treatment time with removing one side of the tether [20].…”
Section: Growth Modulationmentioning
confidence: 99%
“…In 2021, Stevens, Stephens, and Rothberg 23 also described guided growth of the tibial recurvatum by posterior epiphysiodesis of the proximal tibia using the Eight-Plate, with excellent results. Kievit, van Duijvenbode, and Stavenuiter 24 reported a case of knee recurvatum as a complication of treatment of lower limb length discrepancy with temporary epiphysiodesis of the distal femur and proximal tibia using Eight-Plate. The hypothesis is that the recurvate was caused by a very anterior positioning of the plates, and then the correction of the recurved deformity was obtained with the surgical reapproach and posterior replacement of the plates in the distal femur.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Stevens et al (22) described guided growth for tibial recurvatum by posterior proximal tibial epiphysiodesis using eight plates, obtaining excellent results. Kievit et al (23) reported a case in which genu recurvatum was a complication of the treatment of lower limb length discrepancy through temporary epiphysiodesis of the distal femur and proximal tibia with eight plates. The hypothesis is that recurvatum was caused by the very anterior positioning of the plates.…”
Section: Discussionmentioning
confidence: 99%